Digital Competence and Strategic Thinking - Thahrim, Muhammad; Jabid, Abdullah W.; Sirat, Abdul Hadi; Hadady, Hartaty (International Journal of Business, Law, and Education, 2023)
This study aims to examine the relationship between digital competence and strategic thinking. This research was conducted in South Halmahera Regency. The population in this study are businesses located in South Halmahera Regency. The sample in the study was determined based on a purposive sampling approach. The requirements used in this study were that someone in the sample had a position as a small business leader who was already online with a maximum total asset of 500 million rupiah, totaling 179 respondents. Testing the hypothesis in this study using simple linear regression. The results of hypothesis testing show that the hypothesis is supported in this study. Next, recommendations for future research are discussed.